Equilibrium and kinetic modelling of adsorption of Rhodamine B on MoS2. (March 2019) - Li, Zizhen; Meng, Xiangchao; Zhang, Zisheng
Graphical abstract: Highlights: MoS2 with different morphologies were prepared with different S precursor. Adsorption capacity of RhB on MoS2 was impressive. Studies on the adsorption mechanism were conducted and discussed. Abstract: The recent emergence of layered MoS2, which is an earth-abundant material, has gained increasing attention in various fields. In this work, MoS2 is fabricated via a simple hydrothermal method with different sulfur precursors. The effect of S source on the morphologies and adsorption capacities of Rhodamine B (RhB) onto MoS2 were investigated. The results indicated that the MoS2 prepared by CH4 N2 S exhibited the highest adsorption capacity. The N2 sorption isotherm indicated that the as-prepared MoS2 -CH4 N2 S is a mesoporous microsphere. In addition, the adsorption process can be well described by the Langmuir isotherm model and the pseudo second-order model. The intra-particle diffusion model was also employed to analyze the adsorption mechanisms, which demonstrated that the intra-particle diffusion within the mesopores played an important role in the overall adsorption process. Based on these results, MoS2 -CH4 N2 S obtained in this work can be served as a promising candidate for dye removal in wastewater.